Pengaruh Limbah Kaca Sebagai Substitusi Agregat Halus terhadap Sifat Mekanik Beton Normal - Haulida Isnaini; Hariyadi Haryadi; Maya Saridewi Pascanawaty (Jurnal Talenta Sipil, 2026)
The increasing development of the construction industry has led to a growing demand for natural aggregates, while the accumulation of non-biodegradable waste glass continues to increase, posing potential environmental problems. One effort to reduce these impacts is to utilize waste glass as a partial substitute for fine aggregate in normal concrete mixtures. This study aimed to analyze the effect of waste glass as a partial replacement for fine aggregate on the mechanical properties of normal concrete, including compressive strength and splitting tensile strength. An experimental method was employed at the Civil Engineering Laboratory of Universitas Muhammadiyah Mataram using cylindrical concrete specimens with dimensions of 100 mm × 200 mm. The waste glass substitution levels were 0%, 10%, 20%, and 30% by weight of fine aggregate. Compressive strength and splitting tensile strength tests were conducted at the age of 28 days using a Compression Testing Machine (CTM). The results showed that the average compressive strength of normal concrete was 16.22 MPa, while the concrete containing 10%, 20%, and 30% waste glass achieved average compressive strengths of 26.37 MPa, 21.74 MPa, and 20.34 MPa, respectively. The highest compressive strength was obtained at the 10% substitution level. Meanwhile, the average splitting tensile strength of normal concrete was 2.01 MPa, whereas the concrete containing 10%, 20%, and 30% waste glass produced average splitting tensile strengths of 2.99 MPa, 2.48 MPa, and 2.20 MPa, respectively. The highest splitting tensile strength was also achieved at the 10% substitution level. Based on these findings, the use of 10% waste glass as a partial replacement for fine aggregate provides the most optimal improvement in the mechanical properties of normal concrete and has the potential to serve as an environmentally friendly alternative material for sustainable construction.